2016
DOI: 10.2298/vsp150124006m
|View full text |Cite
|
Sign up to set email alerts
|

Urinary KIM-1 and AQP-1 in patients with clear renal cell carcinoma: Potential noninvasive biomarkers

Abstract: uKIM-1 was found to be a reliable diagnostic marker of cRCC, based on its significantly increased values before and decreased values after the nephrectomy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
5
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 25 publications
(30 reference statements)
1
5
0
1
Order By: Relevance
“…Despite only evaluating exosomal AQP1 concentrations, their results corroborated previous studies showing AQP1 is downregulated in RCC tissues and has a significant negative correlation with an unfavourable outcome [60,61]. Mijuskovic et al [36] reported that uAQP1 is twofold lower in patients with RCC than healthy volunteers (P = 0.001), and concentrations increased after nephrectomy. The group also stated no significant correlations between uAQP1 levels and prognostic factors.…”
Section: Aquaporin-1supporting
confidence: 77%
See 3 more Smart Citations
“…Despite only evaluating exosomal AQP1 concentrations, their results corroborated previous studies showing AQP1 is downregulated in RCC tissues and has a significant negative correlation with an unfavourable outcome [60,61]. Mijuskovic et al [36] reported that uAQP1 is twofold lower in patients with RCC than healthy volunteers (P = 0.001), and concentrations increased after nephrectomy. The group also stated no significant correlations between uAQP1 levels and prognostic factors.…”
Section: Aquaporin-1supporting
confidence: 77%
“…Seemingly, there are discrepancies in the link between uAQP1 and ccRCC/pRCC presence between external laboratory findings (Table 2). Regardless of the considerably lower study numbers reported by Mijuskovic et al [36] and Raimondo et al [7] compared to the extensive studies carried out by Morrissey et al…”
Section: Aquaporin-1mentioning
confidence: 85%
See 2 more Smart Citations
“…Впоследствии эти наблюдения были подтверждены результатами исследований других авторов [10][11][12][13][14][15]. В ряде публикаций представлены данные, свидетельствующие о том, что при светлоклеточной карциноме почки уровень этого маркера в моче больных достоверно превышает таковой у здоровых лиц, а повышение концентрации KIM-1 в моче коррелирует со стадией заболевания, размером и степенью дифференцировки опухоли [12,13,15]. Содержание KIM-1 в моче больных ПКР снижается после радикальной нефрэктомии [9,12,16].…”
unclassified